Diffusion in fractal landscapes: simulations and experimental studies of tenebrionid beetle movements - Johnson, A.R; Milne, B.T; Wiens, J.A (Ecology (Durham), 1992)
A study examines anomalous diffusion in field studies of Eleodes beetles and in simulations of correlated random walks on maps or real and artificial landscapes. It is shown how diffusion alternates between ordinary and anomalous diffusion depending on movement rules, landscape pattern and the spatial and temporal scales of observation.